2023
DOI: 10.3390/ph16010113
|View full text |Cite
|
Sign up to set email alerts
|

Ciclopirox Olamine Induces Proliferation Inhibition and Protective Autophagy in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma is one of the most common fatal malignancies worldwide. Thus far, the hepatocellular carcinoma prognosis has been bleak due to deficiencies in the identification and diagnosis of early hepatocellular carcinoma. Ciclopirox olamine (CPX) is a synthetic antifungal agent and has been considered as an anti-cancer candidate drug recently, though the detailed mechanisms related to its anti-cancer effect in hepatocellular carcinoma have not yet been revealed. Here, we found that CPX could inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Wan et al [ 9 ] investigated the repurposing of ciclopirox olamine (CPX), a synthetic antifungal agent for treating tinea corporis, tinea pedis, lichen planus and Candida albicans , to cure hepatocellular carcinoma (HCC). In the study, the researchers identified that CPX (1) inhibited the proliferation of HCC cells by arresting the cell cycle, (2) triggered cellular ROS accumulation as well as the downregulation of DJ-1, an oxidative stress sensor responsible for the onset of oxidative stress-related diseases, for example, cancer, neurodegenerative disorders and type 2 diabetes, (3) promoted complete autophagic flux, and (4) induced glycogen clustering in HCC cells.…”
mentioning
confidence: 99%
“…Wan et al [ 9 ] investigated the repurposing of ciclopirox olamine (CPX), a synthetic antifungal agent for treating tinea corporis, tinea pedis, lichen planus and Candida albicans , to cure hepatocellular carcinoma (HCC). In the study, the researchers identified that CPX (1) inhibited the proliferation of HCC cells by arresting the cell cycle, (2) triggered cellular ROS accumulation as well as the downregulation of DJ-1, an oxidative stress sensor responsible for the onset of oxidative stress-related diseases, for example, cancer, neurodegenerative disorders and type 2 diabetes, (3) promoted complete autophagic flux, and (4) induced glycogen clustering in HCC cells.…”
mentioning
confidence: 99%